2019
DOI: 10.1016/j.tcs.2018.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic aspects of semitotal domination in graphs

Abstract: For a graph G = (V, E), a set D ⊆ V is called a semitotal dominating set of G if D is a dominating set of G, and every vertex in D is within distance 2 of another vertex of D. The Minimum Semitotal Domination problem is to find a semitotal dominating set of minimum cardinality. Given a graph G and a positive integer k, the Semitotal Domination Decision problem is to decide whether G has a semitotal dominating set of cardinality at most k. The Semitotal Domination Decision problem is known to be NP-complete for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…Note that the same inapproximability result holds for DOMINATING SET, TOTAL DOMINATING SET and CONNECTED DOMINATING SET [14]. On the other hand, using the natural greedy algorithm for SET COVER, Henning and Pandey [31] showed that SEMITOTAL DOMINATING SET is in APX for graphs with bounded degree: it admits a 2 + 3 ln(∆ + 1) approximation algorithm for graphs with maximum degree ∆. Moreover, they showed that it is APX-complete for bipartite graphs with maximum degree 4 and asked whether the same holds for subcubic graphs.…”
Section: Approximation Hardnessmentioning
confidence: 73%
See 3 more Smart Citations
“…Note that the same inapproximability result holds for DOMINATING SET, TOTAL DOMINATING SET and CONNECTED DOMINATING SET [14]. On the other hand, using the natural greedy algorithm for SET COVER, Henning and Pandey [31] showed that SEMITOTAL DOMINATING SET is in APX for graphs with bounded degree: it admits a 2 + 3 ln(∆ + 1) approximation algorithm for graphs with maximum degree ∆. Moreover, they showed that it is APX-complete for bipartite graphs with maximum degree 4 and asked whether the same holds for subcubic graphs.…”
Section: Approximation Hardnessmentioning
confidence: 73%
“…Henning and Pandey [31] showed that SEMITOTAL DOMINATING SET has the same approximation hardness as the well-known SET COVER: SEMITOTAL DOMINATING SET is not approximable within (1 − ε) ln n, for any ε > 0, unless NP ⊆ DTIME(n O(log log n) ). Note that the same inapproximability result holds for DOMINATING SET, TOTAL DOMINATING SET and CONNECTED DOMINATING SET [14].…”
Section: Approximation Hardnessmentioning
confidence: 99%
See 2 more Smart Citations
“…We show that the decision version of the MINIMUM PAIRED DOMINATION problem is NP-complete for GP4 graphs, but the MINIMUM SEMIPAIRED DOMINATION problem is easily solvable for GP4 graphs. The class of GP4 graphs was introduced by Henning and Pandey in [15]. Below we recall the definition of GP4 graphs.…”
Section: Complexity Difference Between Paired Domination and Semipairmentioning
confidence: 99%